Analisis Faktor-Faktor Yang Mempengaruhi Penyerapan Tenaga Kerja Sektor Industri Besar Dan Sedang Di Kota-Kota Provinsi Jawa Tengah Tahun 2010-2014 - Firmansyah, Hendri, Dr. Daryono Soebagyo, M.Ec (2017)
This study aims to mngetahui factors that affect employment of large and medium industries in the cities of Central Java province in 2010-2014. And how big factors that affect employment of large and medium industries in the cities of Central Java province in 2010-2014 was influential. The analytical tool used is multiple linear regression on the data panel, by retrieving data using secondary data derived from the library, books, websites, journals or reports of similar studies and of the agency or institution related such as the Central Bureau of Statistics ( CPM), Regional Development Planning Board (Bappeda) These results indicate that the minimum wage of employees, the number of business units, and PRDB partially influence on employment, while the unemployment rate is partially affected. The minimum wage employees, the number of business units, the unemployment rate and PRDB together greatly affect employment. Minmum wages of employees, number of business units, the unemployment rate, and PRDB able to explain the employment of 55.2819%. Thus the government should pay attention to minimum wage employees, the number of business units, and PRDN that employment is getting better.